Music Listening as a Strategy for Managing COVID-19 Stress in First-Year University Students - Vidas, Dianna; Larwood, Joel L.; Nelson, Nicole L.; Dingle, Genevieve A. (Frontiers in Psychology, 2021)
The COVID-19 pandemic brought rapid changes to travel, learning environments, work conditions, and social support, which caused stress for many university students. Research with young people has revealed music listening to be among their most effective strategies for coping with stress. As such, this survey of 402 first-year Australian university students (73.9% female, Mage = 19.6; 75% domestic and 25% international) examined the effectiveness of music listening during COVID-19 compared with other stress management strategies, whether music listening for stress management was related to wellbeing, and whether differences emerged between domestic and international students. We also asked participants to nominate a song that helped them to cope with COVID-19 stress and analysed its features. Music listening was among the most effective stress coping strategies, and was as effective as exercise, sleep, and changing location. Effectiveness of music listening as a coping strategy was related to better wellbeing but not to level of COVID-19 related stress. Although international students experienced higher levels of COVID-19 stress than domestic students, wellbeing was comparable in the two cohorts. Nominated songs tended to be negative in valence and moderate in energy. No correlations were found between any self-report measure and the valence and energy of nominated coping songs. These findings suggest that although domestic and international students experienced different levels of stress resulting from COVID-19, music listening remained an effective strategy for both cohorts, regardless of the type of music they used for coping.